High oxidative stress and decrease of mitochondrial DNA copies in musculoskeletal tumors. - Tanpaisankit , M.; Hongsaprabhas, C.; Charoenlap , C.; Honsawek, S. (Chulalongkorn Medical Journal, 2023)
Background : Musculoskeletal tumors encounter the complications at the diagnosis, treatment, and monitoring with increased prevalence every year. Recently, several studies have shown the association between the modifications in the number of copies of mitochondrial DNA (mtDNA) with cancer progression. However, few studies report the comparison between neoplastic tissues, non-neoplastic tissues, and peripheral blood leukocytes (PBLs) in musculoskeletal tumors. Objectives : The purpose of this study was to investigate the relationship between the number of copies of mtDNA in neoplastic tissues, non-neoplastic tissues, and PBLs of musculoskeletal tumor patients with PBLs of healthy controls. The second aim was to examine the 8-hydroxydeoxyguanosine (8-OHdG) levels in neoplastic tissues and non-neoplastic tissues. Methods : Neoplastic tissues, non-neoplastic adjacent tissues, and venous blood samples were obtained from 48 musculoskeletal tumors patients who underwent surgical removal of their tumors. Peripheral blood was also collected from 100 healthy controls. The number of copies of mtDNA was assessed using quantitative real-time polymerase chain reaction and 8-OHdG levels were investigated by enzyme-linked immunosorbent assay. Results : The number of mtDNA copies in neoplastic tissues significantly decreased when compared with that in non-neoplastic tissues (P = 0.018). In addition, the number of mtDNA copies in PBLs was lower than that in neoplastic tissues (P <0.001) and that in adjacent tissues (P <0.001). The finding showed the number of mtDNA copies in PBLs of the patients was markedly less than that of the controls (P = 0.039). Moreover, the number of mtDNA copies in neoplastic tissues was significantly associated with those in PBLs of the individuals (r = 0.348, P = 0.021). The 8-OHdG levels were increased in neoplastic tissues when compared with those in non-neoplastic tissues as well. Conclusion : The declined number of mtDNA copies in neoplastic tissues and those in PBLs of musculoskeletal tumors patients was observed. The association between the number of mtDNA copies in neoplastic tissues and that in PBLs was also observed in this study. Moreover, 8-OHdG levels in neoplastic tissues were higher than those in non-neoplastic tissues. The results indicate that the increase of oxidative stress in tumor environment may affect the reduction of the number of mtDNA copies. The decrease of the number of mtDNA copies is important event in musculoskeletal tumors progression and might be used as an indicator to identify the tumor development.